Considerations on Boron Neutron Capture Therapy - Campos, Tarcisio Passos Ribeiro de (2000)
This article reviews the radiotherapy technique called Boron Neutron Capture Therapy - BCNT. Herein, basic concepts in BNCT are addressed, particularly how BNCT has been used in the attempts of defeating multiform glioblastoma. The history of the BNCT trials in the 50’s and 60’s, including the previous trials at Brookhaven National Laboratory (BNL) and at the Massachusetts Institute of Technology (MIT) are presented. The Japanese experience in BNCT is discussed. Recently, clinical trials at the MIT and BNL have started, focusing multiform glioblastoma and peripheral and intracranial melanomas. Radiobiological and clinical data from Phase I trials on MIT are discussed. Considerations in how BNCT can be developed in Brazil are presented. It shows that Cf-252 Brachytherapy coupled with NCT may be a non-expensive, alternative way of addressing BNCT.